"The role of quality costs in reducing the cost of industrial" products - الموسوي, يحيى علي; كاظم, هبة سعد (Journal of Economics and Administrative Sciences, 2019)
Abstract :-The aim of the research is to explain the role of quality costs their  importance and their classification, and to clarify the most important tools that help to reduce costs.In order to achieve the objective of the research and test hypotheses adopted the descriptive approach, as well as the adoption of the analytical approach in the study of applied data has been relied upon in providing data on the financial and production reports of the research sample company, the data were used to study and analyze financial and productivity reports . A number of conclusions have been reached the most important being the following:• There is decrease in the cost of prevention in the company the research sample included the costs of planning , product design, training costs ,quality information costs ,preventive maintenance costs, and internal audit costs, Therefor the total cost of prevention between 2015 and 2016 decreased by 31%, this indicator is not good and negatively affects the quality of the cooled engine production.                                                                                                              • Most of internal failure costs in the company were the sample of the research because the stages of manufacturing are done manually and obsolete machines and lack in manufacturing of high quality which is one of the reasons for the percentage of damage and defects in the production phase.